Memória e tradição ao som do Zabumba e do Ganzá: a família Benedito e a relação com a cultura popular de Cabedelo-PB (1952 - 2013) - Targino, Vanusa Diniz (2018)
In our research, we seek to perceive the cultural identity of those who make and live the culture, who transforms and strengthens these cultural manifestations, having as its main focus the individual, the indispensable element to cultural groups, the master. We chose to tell the story of the Benedito family, analyzing the relationship with the culture of Cabedelo, we looked for answers about how was the performance of the masters Benedito and Domerina in the cultural life of Cabedelo, as the relation of these masters with the popular culture and how the profile of a master. In order to base our studies, we sought to know the conceptions of culture through the debate on Cultural History in Peter Burke (2008), we worked on the concept of memory through the studies of Le Goff (1990) and Bosi (1994), who guided us by the memory paths of our collaborators in the research. These narratives, elaborated from memory on the life of the masters Benedito and Domerina, helped to construct a biographical account based on the conceptions of Priore (2009), Avelar and Schmidt (2012). We use the methodology of Oral history, through the conceptions of Meihy and Holland (2015). The work is structured in three chapters: the first chapter focuses on the city, the place of action of cultural groups, already in the second chapter we present the individual, the one who lived the culture in their daily lives, the masters of culture, and for the third chapter, to present the relation of the individual with the popular culture. Finally, we came to the final considerations, where we observed that the participation in the organization of the various cultural groups and the dedication to the local culture were decisive for the recognition of the masters as important figures in the cultural history of the city.